Evaluation of Traffic Impact of Tourism Attraction Development Gajah Mungkur Reservoir, Wonogiri Regency - Amal, Mohammad Fatkhul; Sunarjono, Sri; Rum Harnaeni, Senja (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The Gajah Mungkur Reservoir is one of the popular destinations by the people of Wonogiri. The Regional Government of Wonogiri Regency plans to develop the Gajah Mungkur Reservoir in 2024. The development plan for the Gajah Mungkur Reservoir is predicted to have the potential to have potential impact on decreasing the performance of the road network and intersections in the surrounding area, so a study is needed regarding the current performance of parking, road networks and intersections, current generation and attraction, parking performance, road and intersection networks after development and handling traffic impacts due to development. The analysis method uses MKJI 1997. Based on the results of the analysis, it can be seen that the performance of Jalan Wonogiri - Manyaran - Blimbing/Bts. Provinsi DIY (B-T) in the 2023 Existing condition has a saturation degree of DS=0.43 with a service level of